East Indian Priest, Trinidad, B.W.I. - (:unkn) unknown (Maillard's, Port of Spain, Trinidad; Printed in Germany, 2008)
Photo of an East Indian holy man with an opened book in his hands and his feet on a wooden stool.
Colour: Balck and White; Style: Portrait; Other: Unbordered, Divided
Keywords: Postcards; Hindu priests--Trinidad and Tobago; East Indians--Trinidad and Tobago; 1919; Men--Trinidad and Tobago; Trinidad and Tobago; Ethnic costume--India